Implementation of online cognitive behavioral therapy for insomnia (CBT-i) in Malaysia : a narrative review - Norilani Ali; Shazli Ezzat Ghazali; Ponnusamy Subramaniam; Zaini Said; Noh Amit (Penerbit Universiti Kebangsaan Malaysia, 2021)
Insomnia is a highly prevalent sleep disorder with a high burden of diseases and high comorbidity. Cognitive behavioral therapy for insomnia (CBT-i) is effective but is rarely offered due to the limited access, time constraints, and financial constraints. The inability to treat insomnia has the potential to leave a significant impact in life. Therefore, CBT-i delivered through internet is thought to be more feasible and accessible alternative. The current paper reviewed is based on the narrative review approach. The relevant articles were obtained through computerized searches of databases such as PubMed, SAGE, and ERIC. The findings of this paper highlight the effectiveness of CBT-i based on empirical evidence of previous studies. The focal variables are on sleep hygiene and education, stimulus control therapy, sleep restriction therapy, and relaxation techniques. Having a better understanding how online CBTi works can provide more input for intervention management.